Convergence of Art and Technology in Character and Space Design with Blender - Savaş Sarıhan; Caner Şengünalp (Art Time)
Blender is a 3D modeling and animation software widely used especially in the field of character and space design. This program, which helps users realize their creative ideas thanks to the harmonious combination of art and technology, allows the creation of virtual reality models, simulation, visual effects, stage lighting, game design and many other digital works. Using the features provided by the Blender software, individuals have the ability to craft unique designs and efficiently employ character animation techniques. In this conrtext, artists can nurture their imaginative and unique concepts, merging them with technical prowess through the utilization of the Blender software. Moreover, they can organize their production methods within the framework of embracing the contemporary artistic landscape in the digital era. This article aims to emphasize that the Blender program creates a space that combines art and technology in the same environment by addressing its relationship with art. While reviewing the art created in the digital environment, the research emphasizes the positive or negative aspects and the dimension of temporal gain, especially on the plastic arts and many other industries. In this research, which is carried out as a case study, it is aimed to experience the potential and competence of the Blender program in the production process of digital drawing applications made by various undergraduate design department students in many industrial fields and artistic disciplines.